The Routledge Handbook of Religious Literacy, Pluralism, and Global Engagement - Seiple, Chris; Hoover, Dennis R. (Routledge International Handbooks, 2022)
This pioneering handbook proposes an approach to pluralism that is relational, principled, and non-relativistic, going beyond banal calls for mere ""tolerance."" The growing religious diversity within societies around the world presents both challenges and opportunities. A degree of competition between deeply held religious/worldview perspectives is natural and inevitable, yet at the same time the world urgently needs engagement and partnership across lines of difference. None of the world's most pressing problems can be solved by any single actor, and as such it is not a question of if but when you partner with an individual or institution that does not think, act, or believe as you do. The authors argue that religious literacy-defined as a dynamic combination of competencies and skills, continuously refined through real-world cross-cultural engagement-is vital to building societies and states of neighborly solidarity and civic fairness. Through examination, reflection, and case studies across multiple faith traditions and professional fields, this handbook equips scholars and students, as well as policymakers and practitioners, to assess, analyze, and act collaboratively in a world of deep diversity. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.